Fabrication of Graphene Oxide for Application in Removing Tetracycline Hydrochloride in Aqueous Solution - Nguyen, Thu Huong; Vo, Quang Linh; Nguyen, Ngoc Thinh; Le, Dieu Thu; Tran, Thi Thu Huyen; Nguyen, Minh Viet; Le, Van Dung; Tran, Vinh Hoang; Vu, Anh Tuan (JST: Engineering And Technology For Sustainable Development, 2024)
Recently, antibiotic pollution has been recognized as an aquatic environmental pollution, due to its potential adverse effects on ecosystems and human health. Therefore, it is necessary to have an effective and environmentally friendly method to remove antibiotic residues in the aquatic environment. In this study, Graphene oxide (GO) was synthesized for the treatment of antibiotic residues in the aquatic environment. The characteristics of GO material were analyzed by the X-ray diffraction (XRD), Scanning electron microscopy (SEM), and Transmission electron microscopy (TEM, JEM-JEOL 2100) methods. The GO material was used for the adsorption of tetracycline hydrochloride (TCH) in an aqueous environment. The adsorption equilibration time is 30 min and an efficiency of approximately 88.57% with an initial TCH concentration of 20 mg/L. The factors that affect the adsorption process were investigated including the initial TCH concentration (10 to 40 mg/L), the GO dosage (0.1 to 0.5 g/L), and the pH solution (1 to 9). The adsorption process of TCH on GO material is consistent with the Freundlich isotherm model with a maximum adsorption capacity of 65.65 mg/g. The TCH adsorption process of GO material is exothermic.